2020
DOI: 10.1101/2020.05.01.072611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced meningeal lymphatic drainage ameliorates neuroinflammation and hepatic encephalopathy in cirrhotic rats

Abstract: Background and aimsHepatic encephalopathy (HE) is a serious neurological complication in patients with liver cirrhosis. Nothing is known about the role of the meningeal lymphatic system in HE. We tested our hypothesis that enhancement of meningeal lymphatic drainage could decrease neuroinflammation and ameliorate HE.MethodsA 4-week bile duct ligation (BDL) model was used to develop cirrhosis with HE in rats. Brain inflammation in patients with HE was evaluated using archived GSE41919. Motor function of rats wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Delivery of lymphangiogenic factors, such as VEGF-C, to targeted organs has been shown to reduce inflammation in a variety of disease models. 6,[14][15][16][17][18] For example, virus-mediated delivery of VEGF-C alleviated chronic skin inflammation, 15 inflammatory bowel disease, 16 tubulointerstitial nephritis 17 and hepatic encephalopathy 33 in experimental models using mice or rats. In a mouse model of psoriasis-like skin inflammation, targeted delivery of VEGF-C to sites of inflammation led to a significant increase of lymphatic vessels in inflamed skin and improved lymphatic drainage function.…”
Section: Lymphatic-modulation As Potential Therapymentioning
confidence: 99%
“…Delivery of lymphangiogenic factors, such as VEGF-C, to targeted organs has been shown to reduce inflammation in a variety of disease models. 6,[14][15][16][17][18] For example, virus-mediated delivery of VEGF-C alleviated chronic skin inflammation, 15 inflammatory bowel disease, 16 tubulointerstitial nephritis 17 and hepatic encephalopathy 33 in experimental models using mice or rats. In a mouse model of psoriasis-like skin inflammation, targeted delivery of VEGF-C to sites of inflammation led to a significant increase of lymphatic vessels in inflamed skin and improved lymphatic drainage function.…”
Section: Lymphatic-modulation As Potential Therapymentioning
confidence: 99%
“…For example, Hadjihambi et al found GS dysfunction in several brain regions (olfactory bulb, prefrontal cortex, and hippocampus) in cirrhotic rats with HE, which was closely associated with cognitive dysfunction [15]. Hsu et al found that the improvement of meningeal lymphatic function facilitates glymphatic circulation, enhancing waste removal and thereby alleviating HE [14]. HE is a severe stage of cirrhosis, frequently accompanied by severe complications, such as cognitive impairment and cerebral metabolic dysfunction [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when the GS is dysfunctional, brain metabolites will not be cleared e ciently, which may lead to the adverse progression of neurocognitive diseases such as Parkinson's disease (PD) and Alzheimer's disease (AD) [8,12,13]. In addition, studies have shown that dysfunctional GS plays an important role in the development of hepatic encephalopathy (HE) [14][15][16]. For example, Hadjihambi et al found GS dysfunction in several brain regions (olfactory bulb, prefrontal cortex, and hippocampus) in cirrhotic rats with HE, which was closely associated with cognitive dysfunction [15].…”
Section: Introductionmentioning
confidence: 99%